Biochemical and Immunological Effects of Listeria monocytogenes Hemolysin - Kingdon, G. Charles (1970)
The biochemical and immunological effects of Listeria monocytogenes hemolysin in CD-1 mice were studied. Intraperitoneal injection of 256 complete hemolytic units (CHU) caused a twofold increase in plasma β-glucuronidase levels but was not lethal. In contrast, 256 or more CHU caused 100% lethality in 4 to 5 min when administered intravenously. Intravenous administration of 50 CHU caused a 10- to 11-fold increase in plasma β-glucuronidase levels and was lethal for a variable percentage of the animals. Carbon clearance experiments showed the phagocytic index to be depressed by relatively small amounts of intravenously administered hemolysin and suggested that hemolysin may function as a leucocidal agressin during listeric infection. Increased plasma levels of ornithine carbamyltransferase after intravenous injection of hemolysin indicated hepatocellular damage. Liver carbohydrate and blood glucose determinations on fasted mice showed a reduced gluconeogenic capability in hemolysin-treated animals. Mice immunized with purified hemolysin or live vaccine were more resistant to several of the toxic parameters studied. The data indicate that hemolysin is produced during listeric infection and is antigenic, but not necessarily a protective immunogen.